Ethno-Gamification Platform for Mathematics Learning Based on Balinese Local Wisdom Challenges - I Ketut Lokasanti; Dewa Gede Hendra Divayana; I Gde Wawan Sudatha; I Wayan Sukra Warpala; I Ketut Lokasanti; Dewa Gede Hendra Divayana; I Gde Wawan Sudatha (Universitas Negeri Malang, 2026)
The gap between the abstraction of middle school mathematics material and the real-life challenges faced by students in Bali creates an urgent need to implement a pedagogical innovation that not only utilises technology but is also rooted in the local Balinese cultural context to reduce declines in learning motivation and math anxiety in middle school. The purpose of this research is to develop an Ethno-Gamification Platform as a medium for mathematics learning, based on the challenges of local Balinese wisdom, for junior high school students. This research is a development study using the Borg and Gall development model, modified into five main stages: research and field data collection, planning, design development, initial testing, and revision of initial testing. The research subjects were selected using the Purposive Sampling technique, which involved IT experts, education experts, IT education evaluators, teachers, and junior high school students in Bali. The data collection technique in this study employed a 5-point Likert-scale questionnaire. The data analysis technique applied is a quantitative descriptive approach, using a percentage calculation formula to categories the platform's level of validity and effectiveness. The research shows that the effectiveness of the Ethno-Gamification Platform for Mathematics Learning Based on Local Wisdom Challenges in Bali is 86.5%, categorising it as very effective. This research successfully developed the Ethno-Gamification Platform as a highly effective, innovative, and responsive medium for teaching mathematics based on local wisdom challenges in Bali for junior high school students.